The Relationship Between user Participation In The Architectural Design and the Quality of Residential Buildings In Latakia - Alshaikh, Ramzi; Mannon, Mohammed; Khoder, Ranim (Latakia University Journal -Engineering Sciences Series, 2017)
يعتبر المسكن هو الفراغ الذي يقي الإنسان من العوامل الخارجية ويوفر له احتياجاته الضرورية, ووفقاً لاعتمادات المعترف عليها عالمياً وما بينته الأبحاث العالمية في هذا النطاق فإن أهم مقياس لجودة تصميم المبنى السكني هو درجة الرضا التي يحققها المبنى للمستخدم, وبما أن المستخدمين هم أول من يتأثر بقرار التصميم الخاص بسكنهم يحق لهم المشاركة في عملية اتخاذ القرار في التصميم. يقدم البحث دراسة ميدانية حول مشاركة المستخدم في تصميم المباني السكنية في مدينة اللاذقية, بهدف التحقق من تأثير مشاركة المستخدم على جودة تصميم المبنى السكني عن طريق قياس العلاقة بين درجة مشاركة المستخدمين ومقدار رضاهم عن مساكنهم. خلص البحث إلى أن مشاركة المستخدم لها دور إيجابي في رفع جودة تصميم المبنى السكني في مدينة اللاذقية, بما يتلاءم مع الإمكانات المتاحة . Housing is considered void that protects the rights of the external factors and provide him with the necessary requirements, and depending on the quality and the pioneers of global research in this range, the most important measure of the quality of the residential building is the degree of satisfaction achieved by the building of the user , Since users are the first to be affected by the decision of the house's design to understand they have the right to participate in decision-making in the design process. The research presents a field study on the posts in the design of residential buildings in the city of Latakia in order to check the impact of user participation on the quality of the residential building designed by measuring the relationship between the degree of user participation and the amount of satisfaction from their homes. The research found that the user has the participation of a major role in raising the quality of the design of the apartment building in the city of Latakia in line with available resources.